Is the Informal Sector Constrained from the Demand Side? Evidence for Six West African Capitals - Rainer Thiele; Marcus Böhme (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Employing a unique dataset that covers households from six West African capitals, this paper provides new evidence on the demand for informal sector products and services. We first investigate whether demand linkages exist between formal and informal products and distribution channels, and whether there is an overlapping customer base, which would imply that both formal sector wage earners and informal workers buy both formal and informal products using both formal and informal distribution channels. In a second step, we estimate demand elasticities based on Engel curves. We find a strongly overlapping customer base and strong demand-side linkages between the formal and informal sector, with the exception that informal goods are hardly bought through formal distribution channels. The estimated demand elasticities tend to show that rising incomes are associated with a lower propensity to consume informal sector goods and to use informal distribution channels. We therefore conclude that the informal sector in West Africa is likely to be constrained from the demand side.
Keywords: D12; O17; 330; Informal sector; formal-informal linkages; Engel curve estimates; West Africa